2013
DOI: 10.5152/akd.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid functions after contrast agent administration for coronary angiography: a prospective observational study in euthyroid patients

Abstract: Objective: This study aims to investigate long-term effects of iodinated radiographic contrast media used for coronary angiography (CAG) on the thyroid function in euthyroid patients. Methods: In a prospective observational cohort study, nonionic iodinated contrast material was electively used in 101 patients for coronary angiography. The patients were recruited without age restrictions and, at baseline, all had normal levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyrotropin (TSH). The morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
15
1
1
Order By: Relevance
“…On the other hand, a couple of recent studies suggest relevant clinical effect of iodine load by angiography. A study from Turkey reported a rate of thyrotoxicosis after 4 and 8 weeks from ICM, not different from that observed in this study. The second is an interesting large case–control study: over a 20‐year period, patients without dysfunctional thyroid diseases had a 2‐3 fold increased risk of developing hyperthyroidism following exposure to iodine load by angiography as compared to those were not exposed.…”
Section: Discussioncontrasting
confidence: 91%
“…On the other hand, a couple of recent studies suggest relevant clinical effect of iodine load by angiography. A study from Turkey reported a rate of thyrotoxicosis after 4 and 8 weeks from ICM, not different from that observed in this study. The second is an interesting large case–control study: over a 20‐year period, patients without dysfunctional thyroid diseases had a 2‐3 fold increased risk of developing hyperthyroidism following exposure to iodine load by angiography as compared to those were not exposed.…”
Section: Discussioncontrasting
confidence: 91%
“…64,65 A Turkish study of 101 patients who underwent coronary angiography found a small increased risk of subclinical hyperthyroidism at up to 8 weeks after the iodine exposure. 66 However, one small study showed that intravenous administration of an iodine contrast agent during pregnancy did not result in a notably increased incidence of fetal thyroid dysfunction. 67 Finally, we have reported the occurrence of iodine-induced hypothyroidism in three neonates who received intravenous contrast agents to evaluate congenital cardiac defects.…”
Section: Sources Of Iodine Excessmentioning
confidence: 99%
“…Iodine levels in the body will remain elevated after digestion of iodinated contrast, and it can take more than one month for iodine levels to be normalized following exposure [45]. Case reports [46,47,48,49] and the results of a large case-control study [50] support the premise that using iodinated contrast is a potential risk factor for the development of acute iodine excess and thyroid disorders. Thus, even a one-time of ingestion of any of these sources can lead to dangerous acute iodine excess.…”
Section: Iodine: An Abundant and Easily Accessible Environmental Rmentioning
confidence: 99%